Influence of Clostridium butyricum inoculum age on glycerol fermentation / Influência da idade do inóculo de Clostridium butyricum na fermentação de glicerol - Corrêa, Mariana F. D. (2020)
The high production of biodiesel in recent years has generated a large amount of crude glycerol that cannot be absorbed and totally process in the industry. In this way, new studies focused on using this residue have become important to promote the development of biodiesel industry. The 1,3- propanediol (1,3-PDO) is an organic compound with bifunctional character that has great potential to be used in several reactions of polymer synthesis. It is usually used in polycondensation to produce polyesters, polyurethanes and polyethers. 1,3-propanediol (1,3-PDO) and organic acids are simultaneously produced by Clostridium butyricum growing on glycerol. The purpose of this study was to evaluate the growth kinetics of Clostridium butyricum on glycerol-based medium and to observe the influence of inoculum age on the product formed, such as 1,3-propanediol and butyric acid. The results showed the kinetic stages of the Clostridium butyricum growing on glycerol, however no significant difference between the products formed was observed in different conditions studied.